2022
DOI: 10.1021/acs.jnatprod.1c00971
|View full text |Cite
|
Sign up to set email alerts
|

Selaginellin Inhibits Melanogenesis via the MAPK Signaling Pathway

Abstract: Hyperpigmented skin diseases such as melasma, freckles, and melanosis usually mar the appearance of patients. Traditional herbal medicines are highly accepted in inhibiting skin pigmentation, with advantages of high efficiency, low cost, and low side effects. Selaginellin (SEL), one of the active compounds of selaginella, has been proved to be exhibit antineoplastic, antioxidant, antisenescence, and antiapoptosis activities. In this study, we found that SEL can inhibit melanogenesis in vitro and in vivo. A mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Zhou et al reported that Selaginellin (SEL) inhibited the mitogen-activated protein kinase (MAPK) signaling pathway. Then, the expression of microphthalmia-associated transcription factor (MITF ) and the downstream genes tyrosinase ( TYR ) and tyrosinase-associated protein 2 ( TYRP2 ) were downregulated to inhibit melanin production [ 26 ]. Interleukin-10 (IL-10) can activate the PI3K/Akt and JAK/Stat3 pathways, and the former leads to the activation of the classical NF-κB pathway and the inactivation of GSK-3β, further upregulating melanin production [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al reported that Selaginellin (SEL) inhibited the mitogen-activated protein kinase (MAPK) signaling pathway. Then, the expression of microphthalmia-associated transcription factor (MITF ) and the downstream genes tyrosinase ( TYR ) and tyrosinase-associated protein 2 ( TYRP2 ) were downregulated to inhibit melanin production [ 26 ]. Interleukin-10 (IL-10) can activate the PI3K/Akt and JAK/Stat3 pathways, and the former leads to the activation of the classical NF-κB pathway and the inactivation of GSK-3β, further upregulating melanin production [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of MAPK signaling is a promising way to develop agents for hyperpigmentation disorders [ 15 ]. In previous studies, some herbal extracts, such as selaginellin [ 16 ], isoliquiritigenin [ 17 ], can inhibited melanogenesis by deactivating ERK. Fraxin has also been reported to down-regulate ERK protein phosphorylation to protect hepatocytes from carbon tetrachloride (CCL4)-induced damage and to antagonize cerebral ischemia-reperfusion injury [ 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methanolic extract of L. shawii leaves at the lowest tested concentration (i.e., 7.8 μg/mL), displayed a significant increase in human melanocyte proliferation without causing cytotoxicity at high concentrations (i.e., 500.0 μg/mL), and its effect was evaluated using additional experiments related to melanogenesis. Of note, skin melanocyte functions such as migration, proliferation, and melanogenesis are regulated by a complex network of extrinsic and intrinsic signaling pathways, including the mitogen-activated protein kinase (MAPK) pathway and its downstream effector MITF, a transcription factor of melanogenesis-related gene expression ( Zhou et al, 2022 ). In addition, L. shawii , also known as the Arabian boxthorn, is a thorny shrub mainly found in the Arabian Peninsula.…”
Section: Discussionmentioning
confidence: 99%